Hubungan Intensitas Kebisingan dengan Tingkat Kelelahan pada Pekerja Departemen Produksi Perusahaan Pipa Baja di Surabaya - Gregorius Jeffry Pangaribuan; Noeroel Widajati (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Noise in the workplace is one of the factors associated with work fatigue. The purpose of this study was to examine the relationship between work fatigue and noise levels among workers in the production department of a steel pipe company in Surabaya. The sample in this study consisted of 55 workers selected through total sampling. The research design was quantitative with a cross-sectional approach. The independent variable in this study was noise intensity and the dependent variable was work fatigue levels. The analysis used was the contingency coefficient using the SPSS application. The results showed that noise intensity and work fatigue levels had a significant relationship with a p-value = 0.003 (<0.005) and a contingency coefficient (C) of 0.452, indicating a moderate relationship. This study suggests that companies apply noise mapping as a reference for workers so that they can prevent the adverse effects of high noise, especially on increased work fatigue.